The 2001 Institute of Cistercian Studies Conference - Krieg, Martha F. (Cistercian studies quarterly, 2001)
Highlights the Cistercian Studies conference held on May 3, 2001 at the Fetzer Center, Western Michigan University, Kalamazoo, Michigan. Beginnings of the Medieval Convocation; Presenter of the inaugural paper; Concept of vocations to monastic life; Thought and influence of the monk Bernard of Clairvaux.